G259(P) Hypercalcaemia- a herald sign of leukaemia in children. (7th April 2014) - Kundagrami, S; Kamhieh, Y; Mukherjee, K; Datta, M
Abstract : We present an interesting case of a 12 year old boy who presented with features of renal failure and hypercalcaemia who was later diagnosed with acute lymphoblastic leukaemia. This young man with no significant past medical history presented to hospital with a short history of vomiting and features of moderate dehydration following a school trip to Menorca. Initial biochemical investigations revealed hypercalcaemia and pre-renal failure. Platelet count was low at 115 but rest of the full blood count and blood film was normal. Fluid resuscitation was commenced to correct dehydration. Despite fluid therapy and good urine output hypercalcaemia persisted and creatinine levels increased. Tertiary paediatric renal opinion was sought and accordingly Parathyroid hormone levels were noted to be low, furosemide and aggressive fluid resuscitation was continued. An abdominal ultrasound did not reveal any renal abnormalities or other abdominal masses. Further management was continued in the tertiary unit; the renal function improved, hypercalcaemia persisted requiring treatment with calcitonin. Bone scan was normal, serum parathyroid levels however continued to be low. Thyroid ultrasound scan revealed a single hypoechoic region behind the right lobe of the thyroid. The child was discharged with a presumed functioning parathyroid nodule, and an outpatient SPECT CT was subsequently reported to be normal. The young man represented three weeks after discharge with history of generalised fatigue and low grade fever. Clinical examination revealed splenomegaly. A blood count then showed pancytopaenia and blast cells in the blood film. The paediatric oncology team diagnosed him with acute lymphoblastic leukaemia. This case is unique in its early presentation of acute lymphoblastic leaukaemia with significant hypercalcemia which preceded the clinical and haematological features of malignancy in peripheral blood film. There have been few reports of cases of initial hypercalcaemia in a minority of cases of acute leukaemia (approximately 0.6%) in children. Unexplained hypercalcaemia in the paediatric population should therefore be treated with caution: these children need regular clinical and biochemical monitoring to exclude malignancy.